NATIONAL UNITY AT THE UNIVERSITY LEVEL: IMPORTANCE OF CIVILISATIONAL DIALOGUE AND WAY FORWARD - Lee Wei Chang; Baharuddin Azizan; Muhammad Amran (European Scientific Journal, ESJ, 2014)
Malaysia is often described as a prime example of societies that are severely divided along ethnic lines. The country is also among the few pluralistic societies that have achieved some measure of success in managing ethnic conflict and enjoying relative political stability. Efforts toward integrating the diverse groups in the interest of national unity have been, and remain, at the heart of all Malaysian endeavours for peace (Suhana Saad 2012). Many changes have been introduced. There has been much discussion pointing to the education system as a key place where national unity may be nurtured. This paper however aims at examining the role played by the university in promoting national unity. Mixed mode method has been used to study the various stakeholders’ perspectives in order to identify the current efforts and challenges of promoting national unity at the local universities in Malaysia. Results from the 420 surveys given to university students showed that effort of promoting national unity at the university level is very important and dialogue is said to have play the equal role in promoting national unity as well as to world peace. Results from interview also indicated that focusing on teaching and learning for example via the TITAS/Ethnic Relations Courses to promote national unity may just not suffice. A more interactive and proactive way of teaching and learning should be encouraged in all the university courses so that the good policies/concepts/ideology introduced towards promoting national unity could be fully reflected via practices.